Enhancing Laboratory Sample Collection Efficiency through Laboratory Information Systems: Insights into Optimal Despatch Rider Management - Jasmin, Nur Syafiqah; Ma’on, Siti Noor Suriani; Omar, Muhammad (Information Management and Business Review, 2024)
Effective administration of dispatch riders is crucial for delivering reliable diagnoses and research results by enabling prompt and precise sample collection. Laboratory Information Systems (LIS) offers a solution to enhance the efficiency and organization of dispatch riders in laboratory settings. Thus, the main objective of this study is to provide insights and knowledge on the potential benefits of implementing LIS to optimize the management of dispatch riders and enhance the efficiency of sample collection. An analysis of previous research findings illustrates the varied benefits of using LIS in improving key performance indicators such as turnaround time, mistake rates, and coordination of dispatch riders. The LIS platform serves as a centralized system for managing and allocating sample collection jobs, minimizing scheduling conflicts, and optimizing dispatch rider routes. Real-time tracking capabilities enable laboratory management to monitor dispatch rider locations and sample collection progress, facilitating enhanced coordination and resource allocation. Furthermore, LIS-generated data analytics provide valuable insights into sample collection patterns, enabling proactive management strategies to mitigate potential bottlenecks. Integration of LIS into payroll systems allows for automated compensation calculation based on dispatch rider performance metrics, ensuring fair and transparent pay rates. Studies consistently demonstrate that adequate compensation positively impacts dispatch rider motivation and sample collection effectiveness. This study highlights the vital importance of LIS in enhancing dispatch rider administration for efficient sample collection operations. It provides insights for laboratory managers and policymakers to optimize the potential of LIS to improve operational performance, facilitate patient care, and advance research outcomes.